Становление и развитие основных направлений научной деятельности Донецкого ботанического сада НАН Украины (к 40-летию основания) - Глухов, А.З.; Хархота, А.И. (Промышленная ботаника, 2004)
Forming and development of basic trends of scientific activity of the Donetsk Botanical Gardens, Nat. Acad. Sci. of Ukraine have been shown for the first time on the basis of a brief survey of fundamental scientific researches themes for the whole period of the Gardens’ functioning. Priority trends for the nearest time are determined.